Using morphometric and hydrological data to predict potential floods in the Wadi Al-Dhalimi basin - Abbass , Hamza; Abood , Abdullah (Al-Adab Journal, 2025)
The Wadi Al-Dhalimi basin is one of the seasonal valleys that flow directly into Lake Razzaza, as it slopes from the west towards the east towards its mouth. The basin is formed from an area that reaches an altitude of 214 meters above sea level, with a total length of 41.6 km. The basin itself consists of secondary basins, which are the western basin and the southern basin.A group of natural factors share in the variation of the morphometric and hydrological characteristics of the basin, including geological formations, the oldest of which dates back to the formations of the Tertiary geological period and the most recent of which are deposits of the Quaternary period. As for the climate, the semi-arid climate prevails, characterized by fluctuating rainfall.The study relied on the Snyder Model to estimate the volume of floods and analyze their risks based on the morphometric and hydrological characteristics of the basin.